Effect of inclination and position of new swimming starting block's back plate on track-start performance - Takeda, T.; Takagi, H.; Tsubakimoto, S. (Sports Biomechanics, 2012)
This study investigated the effects of both anterior-posterior position and inclination of a back plate positioned on a starting platform on swimming start performance. Ten male college swimmers performed eight starts with varying combinations of take-off angle (normal and lower), inclination angle (10°, 25°, 45°, and 65°) and position (0.29, 0.44, and 0.59 m from the front edge of the starting block). Two-way repeated measures analysis of variance (ANOVA; take-off angle × back plate) for four conditions with take-off angles (normal and lower) and inclinations (10° and 45°), and one-way ANOVA for comparisons between four inclinations and three positions were carried out. Multiple comparisons were made using Bonferroni's method. The main effects of the take-off angle were on the vertical and resultant take-off velocities [F(1,18) = 36.72, p < 0.001 and F(1,18) = 9.58, p = 0.013, respectively]. Comparisons between the plate positions showed that the 5 m time of the 0.29 m condition was significantly longer, the take-off angle and vertical take-off velocity of the 0.59 m condition were significantly lower, and horizontal and resultant take-off velocities of the 0.29 m condition were significantly less. Rear foot take-off times were significantly longer in the ascending order: 0.29, 0.44, and 0.59 m.